The food retail environment and area deprivation in Glasgow City, UK - Macintyre Sally; Ellaway Anne; Macdonald Laura (BMC, 2009)
Abstract It has previously been suggested that deprived neighbourhoods within modern cities have poor access to general amenities, for example, fewer food retail outlets. Here we examine the distribution of food retailers by deprivation in the City of Glasgow, UK. We obtained a list of 934 food retailers in Glasgow, UK, in 2007, and mapped these at address level. We categorised small areas (data zones) into quintiles of area deprivation using the 2006 Scottish Index of Multiple Deprivation Income sub-domain score. We computed mean number of retailers per 1000 residents per data zone, and mean network distance to nearest outlet from data zone centroid, for all retailers combined and for each of seven categories of retailer separately (i.e. bakers, butchers, fruit and vegetable sellers, fishmongers, convenience stores, supermarkets and delicatessens). The most deprived quintile (of areas) had the greatest mean number of total food retailers per 1000 residents while quintile 1 (least deprived) had the least, and this difference was statistically significant (Chi-square p < 0.01). The closest mean distance to the nearest food retailer was within quintile 3 while the furthest distance was within quintile 1, and this was also statistically significant (Chi-square p < 0.01). There was variation in the distribution of the seven different types of food retailers, and access to amenities depended upon the type of food retailer studied and whether proximity or density was measured. Overall the findings suggested that deprived neighbourhoods within the City of Glasgow did not necessarily have fewer food retail outlets.